Perturbations of Plasmodium Puf2 expression and RNA‐seq of Puf2‐deficient sporozoites reveal a critical role in maintaining RNA homeostasis and parasite transmissibility. (27th February 2013) - Lindner, Scott E.; Mikolajczak, Sebastian A.; Vaughan, Ashley M.; Moon, Wonjong; Joyce, Brad R.; Sullivan, William J.; Kappe, Stefan H. I.
Summary Malaria's cycle of infection requires parasite transmission between a mosquito vector and a mammalian host. We here demonstrate that the Plasmodium yoeliiPumilio‐FBF family member Puf2 allows the sporozoite to remain infectious in the mosquito salivary glands while awaiting transmission. Puf2 mediates this solely through its RNA‐binding domain (RBD) likely by stabilizing or hastening the degradation of specific mRNAs. Puf2 traffics to sporozoite cytosolic granules, which are negative for several markers of stress granules and P‐bodies, and disappear rapidly after infection of hepatocytes. In contrast to previously described Plasmodium berghei pbpuf2− parasites, pypuf2− sporozoites have no apparent defect in host infection when tested early in salivary gland residence, but become progressively non‐infectious and prematurely transform into EEFs during prolonged salivary gland residence. The premature overexpression of Puf2 in oocysts causes striking deregulation of sporozoite maturation and infectivity while extension of Puf2 expression in liverstages causes no defect, suggesting that the presence of Puf2 alone is not sufficient for its functions. Finally, by conducting the first comparative RNA‐seq analysis of Plasmodium sporozoites, we find that Puf2 may play a role in directly or indirectly maintaining the homeostasis of specific transcripts. These findings uncover requirements for maintaining a window of opportunity for the malaria parasite to accommodate the unpredictable moment of transmission from mosquito to mammalian host.